THE INFLUENCE OF LEADERSHIP, MOTIVATION, ORGANIZATIONAL CULTURE, LECTURER COMPETENCE ON LECTURER PERFORMANCE WITH LECTURER DISCIPLINE AS INTERVENING - Nurmawati, Nurmawati; Assagaf, Aminullah; Sukiman, Susanto (LPPM of NAROTAMA UNIVERSITY, 2024)
Objectives: (1) Analyze the influence of leadership, motivation, organizational culture, lecturer competence on lecturer discipline (2) Analyze the influence of leadership, motivation, organizational culture, lecturer competence, lecturer discipline on lecturer performance Design/methodology/approach: This study uses a quantitative approach by distributing questionnaires by sampling. The research data were analyzed using multiple regression Findings: The results showed that (1) leadership correlated significantly very low with lecturer performance of 31.9% (2) lecturer motivation correlated significantly very strongly with lecturer performance of 80.2% (3) organizational culture correlated significantly very strongly with lecturer performance of 78.3% (4) lecturer competence correlated significantly strong with lecturer performance of 56.3%. Practical Implications: This research includes several things, including the lack of optimal discipline and performance of lecturers in carrying out the tridharma of higher education.